1985
DOI: 10.1021/ja00297a020
|View full text |Cite
|
Sign up to set email alerts
|

Structure of rhodium in an ultradispersed rhodium/alumina catalyst as studied by EXAFS and other techniques

Abstract: DOI to the publisher's website. • The final author version and the galley proof are versions of the publication after peer review. • The final published version features the final layout of the paper including the volume, issue and page numbers. Link to publication General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
165
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(188 citation statements)
references
References 6 publications
23
165
0
Order By: Relevance
“…This first step is only partially complete after reduction at 100~ and complete after the same treatment at 200~ The second step involves the removal of residual chlorine from the support, reduction at 300~ is sufficient to decrease the CI-and C10-intensities to typical background levels. Porous alumina-supported catalysts retain considerably more chlorine [4,5], also after reduction at 300~ We think that diffusion limitations and readsorption, which are present in porous but absent in flat supports, may explain the difference in behavior with respect to C1 retention.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This first step is only partially complete after reduction at 100~ and complete after the same treatment at 200~ The second step involves the removal of residual chlorine from the support, reduction at 300~ is sufficient to decrease the CI-and C10-intensities to typical background levels. Porous alumina-supported catalysts retain considerably more chlorine [4,5], also after reduction at 300~ We think that diffusion limitations and readsorption, which are present in porous but absent in flat supports, may explain the difference in behavior with respect to C1 retention.…”
Section: Discussionmentioning
confidence: 86%
“…At low pH, negatively charged complexes may adsorb on the positively charged alumina surface. Chlorine is known to be retained in significant amounts by alumina supports [4,5] and is expected to affect the catalytic properties of rhodium surfaces [6]. In this letter we use static secondary ion mass spectrometry (SIMS) and monochromatic X-ray photoelectron spectroscopy (XPS) to characterize the state of the catalyst in various stages of the preparation, and we investigate in particular whether chlorine residues from the catalyst precursor are in contact with rhodium in the reduced catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…For Rh/TiOz this occurs for metal loadings below 0.5%, and for Rh/ AlZ03 even for metal loadings up to 5%. Although in this study only two catalysts with an H/I& value above unity were investigated, we have reported about other ultradispersed systems elsewhere (32,36). In our opinion, if one accepts that a metal atom such as rhodium can adsorb two or more CO molecules, one should not reject the idea of that same atom adsorbing more than one hydrogen atom.…”
Section: Tem Measurementsmentioning
confidence: 77%
“…Upon CO adsorption the very small rhodium particles are broken up into Rh(I)(CO)z species, which give the twin IR absorption. EXAFS proof for this explanation has been published elsewhere (36).…”
Section: Tem Measurementsmentioning
confidence: 94%
“…CO-induced changes in structure are also known to occur in different types of supported noble metal catalysts (32)(33)(34). Nevertheless, the structure of the activated FeM/SiO 2 catalysts has not yet received much attention.…”
Section: Introductionmentioning
confidence: 99%